A post-modernist critique of community psychology - Isemonger, Ian (PINS-Psychology in Society, 2025)
Community psychology in broad essence is an attempt to re-situate the therapeutic process from the individual to the community at large, therapy addressed to the alienated subject is addressed rather to the alienated community. Implicit in this attempt is the recognition that we cannot uncouple the individual from his/her world, that resources directed at the individual are often misguided treating only the manifestations of some environmental failure. To illustrate this in more concrete terms we might refer to the issue of alienation and delinquency amongst coloured people, in this instance most would endorse the view that efforts directed at individual delinquents do not meet the issue at hand, that the high incidence of alienation and delinquency amongst the coloured people must reflect a shortcoming in the community at large. Although this recognition is a welcome departure from the individualism that has characterized so much of psychology there are consequential intellectual difficulties in shifting this focus from individual to community. One of these is that the concept of community is itself enigmatic there being few objective criteria for the identification of a community. I would like to argue in this article that this is not a worthwhile problem, that if we take the community in the spirit of Anderson (1983) as a mental construct, then we will see this as a resource for the creation of new communities an activity which I will argue is itself therapeutic. I would also like to pursue the idea that the targeting of an existing community for intervention, will in itself lead to the importation into the programme of the ideological and historical precedents to its alienation, and that the more productive means of limiting alienation is the formation of new communities.